Indoor Thermal Comfort Improvement of the Naturally Ventilated House in Tropical Climate, Indonesia - Muhammad Iqbal; Muhammad Dastur; Muhammad Fikry (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Two types of houses in North Aceh, Indonesia, are investigated in this study. Even though the hot and humid conditions throughout the year, most Indonesian stay in a house that uses natural ventilation due to energy poverty and economic conditions. Commonly, they rely on natural ventilation by opening windows to achieve thermal comfort in the indoor environment. Therefore, an on-site survey and questionnaire were performed on more than 240 occupants and 115 naturally ventilated houses to investigate thermal comfort performance between two houses based on thermal sensation vote (TSV) and thermal comfort vote (TCV). In addition, some questions related to thermal preference and body response are employed. This study also examines thermal comfort with a numerical simulations program called THERB for HAM, a coupled analysis software for heat, moisture, and air. The results show that the room comfort level was not optimal, where most occupants' feelings were warm and hot. However, type 1 is more comfortable than type 2, and simulation results confirm indoor environmental conditions. Furthermore, this study presents the adaptive behavior, where most occupants utilize the windows openings in the morning until noon and operate the fans during the night to modify indoor environment conditions to be more comfortable.